Analisis Kepuasan Konsumen terhadap Produk Tinutuan di Kawasan Wisata Kuliner â€œWakekeâ€ Kota Manado - Nancy G. Aipipidely; Gene H.M. Kapantou; Juliana Mandei; Jeane Timban (COCOS, 2014)
ABSRACTNancy Aipipidely. The Consumen Satisfication Analysist of Tinutuan Product in â€œWakekeâ€ Cullinary Tourism Area Manado City. Under guidance of Gene Kapantow as chairman, and Juliana Mandei and Jean Timban as members.The objective of this research is to measure the consumerâ€™s satisfication level of tinutuan in â€œWakekeâ€ cullinary tourism area, based on product, price, location and sevice from the employee who works at the restaurant. The method used in this research is survey method. This research uses primary and secondary data. Primary data are obtained from interviewed with tinutuan consument with questioner to collect the data. Secondary data are obtained from restaurantâ€™s manager/owner. Sampling method used in this research is systematic sampling to 10 consumers in each of 13 restaurant, with total of 130 consumens as respondents. Data analys used in this research is descriptive which analized with Likert Scale and presented in table form.This research result showed that satisfication level of tinutuan consumer in â€œWakekeâ€ cullinary tourism area, based on product, price, location and sevice was the total score of 9706, which means that satisfication level index of 78,6% and classified as satisfied. That means tinutuan consumer satisfy with the product and service given by the employee in restaurants at â€œWakekeâ€ cullinary tourism area. The factor that need to be improved was in maximazing consumer satisfcation was to prepare restaurant facilities in form of available parking lot and physical look improvement by employee who work in restaurant at that area